ENHANCING ZAKAT LITERACY: DEVELOPING A CANVA-ASSISTED E-MODULE TO OVERCOME LEARNING DIFFICULTIES IN ISLAMIC JURISPRUDENCE - Muhammad Zaim; Nurzazin Nurzazin (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2025)
This study aimed to develop a Canva-assisted e-module on zakat for Fiqh learning to address students’ learning difficulties. The study employed a research and Development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were eighth-grade students in the second semester of the 2023/2024 academic year. Data were collected through expert validation (material and media experts) and practicality questionnaires administered to teachers and students. The results indicated that the Canva-assisted Fiqh e-module achieved a validity score of 88% (very feasible) and a practicality score of 87.5% (very practical). In addition, students’ average learning outcomes improved from 68 to 85, indicating high effectiveness. The integration of Canva facilitated interactive, visually engaging, and contextually relevant learning experiences, enabling students to better understand zakat calculations and enhancing their motivation to learn. The findings imply that the developed e-module is suitable as an innovative instructional medium for Fiqh learning and can serve as an alternative solution to help students overcome difficulties in understanding zakat concepts.